Reclaiming Local History for the Development of Historical Consciousness - Asril; Ahmal; Nurdiansyah; Pernantah, Piki Setri (Universitas Pendidikan Ganesha, 2025)
Local history is often marginalized within the grand narrative of national history, resulting in the underrepresentation of regional cultural identities in the collective memory. This condition contributes to the low level of students’ historical consciousness rooted in local experiences and wisdom. This study aims to critically analyze, evaluate the relevance, and formulate a model for integrating local historical heritage into history learning in order to foster historical awareness, cultivate reflective attitudes, and promote the decolonization of knowledge through the application of critical pedagogy. The research employed a qualitative approach with a case study design. The subjects consisted of 6 history teachers, 5 traditional leaders, and 45 high school students, while the research instruments included interview guides, observation sheets, and document analysis formats. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using thematic triangulation techniques to ensure the validity of the findings. The results show that the integration of local history can transform students’ roles from passive recipients into active meaning-makers, strengthen historical consciousness, and create space for critical reflection on dominant historical narratives. The study concludes that history learning based on critical pedagogy can serve as an effective strategy to address the marginalization of local history while simultaneously reinforcing students’ cultural identity. The implications highlight the importance of developing inclusive curricula and transformative pedagogical practices that are relevant to local cultural contexts and enrich the theoretical discourse of critical pedagogy.